2023
DOI: 10.1038/s41419-023-05997-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-induced ribosome collision activates ribosomal surveillance mechanisms

Abstract: Impairment of protein translation can cause stalling and collision of ribosomes and is a signal for the activation of ribosomal surveillance and rescue pathways. Despite clear evidence that ribosome collision occurs stochastically at a cellular and organismal level, physiologically relevant sources of such aberrations are poorly understood. Here we show that a burst of the cellular signaling molecule nitric oxide (NO) reduces translational activity and causes ribosome collision in human cell lines. This is acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…P1 is a component of the P-stalk region on the large subunit of eukaryotic ribosomes and has been shown to play an important role during the elongation stage of protein synthesis [61][62][63]. Under amino acid starvation conditions or in the presence of other cellular stressors, ribosomes collide during mRNA translation [70][71][72]. A recently published cryo-electron microscopy study revealed the structure of GCN1 bound to two colliding ribosomes [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P1 is a component of the P-stalk region on the large subunit of eukaryotic ribosomes and has been shown to play an important role during the elongation stage of protein synthesis [61][62][63]. Under amino acid starvation conditions or in the presence of other cellular stressors, ribosomes collide during mRNA translation [70][71][72]. A recently published cryo-electron microscopy study revealed the structure of GCN1 bound to two colliding ribosomes [73].…”
Section: Discussionmentioning
confidence: 99%
“…Under amino acid starvation conditions or in the presence of other cellular stressors, ribosomes collide during mRNA translation [70][71][72]. A recently published cryo-electron microscopy study revealed the structure of GCN1 bound to two colliding ribosomes [73].…”
Section: Discussionmentioning
confidence: 99%
“…RQC is a translation-dependent mechanism of quality control and more actively translated mRNAs are more prone to ribosome collisions and triggering RQC 2022 , due to the higher chance of presence of trailing ribosomes that collide into a stalled ribosome. Metabolic stress and oxidative agents such as nitric oxide and reactive oxygen species, which are common in cancer cells and directly damage ribonucleotide bases, impede the transition of translating ribosomes and cause ribosome stalling 14,15,56,57 . Furthermore, following oncogenic transformation, overall translation activity is often elevated, partly due to mutation and activation of signalling pathways such as PI3K/mTOR 58 , which stimulate mRNA translation 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has been made in our understanding of the mechanism of RQC 26 , its important role in maintenance of homeostasis 31,32 and triggering global reprogramming of gene expression in response to stress 15,25,32,56,61 . Yet, important gaps exist in our understanding of how the RQC mechanism itself is regulated in response to environmental stimuli that impact cellular metabolism and mRNA translation, including the antimetabolites such as 5FU.…”
Section: Discussionmentioning
confidence: 99%
“…These reagents and UV leave the A-site vacant during translation inhibition. Furthermore, the signaling molecule nitric oxide also activates ISR and RSR via ribosome collision (see below) [ 85 ]. Thus, GCN1–GCN2 and other eIF2α kinases function as sentinels that monitor translational defects and proteostasis via ISR.…”
Section: Emerging Role Of Gcn1 In Co-translational Protein Quality Co...mentioning
confidence: 99%